Posture and Muscle Activity during Waste Collection Work. Issue 1 (4th August 2021) - Netto, Kevin; Francis-Pester, Garry; Lewis, Caleb; Dunnill, Patrina; Darling, Russell
Abstract: The musculoskeletal load in waste collection has been examined through simulated assessment of pulling and pushing bins as well as lifting and throwing rubbish bags. With the onset of mechanization, many of these tasks do not exist and workers are faced with other loads not previously assessed. The purpose of this study was to quantify the postures and muscle activity during mechanized waste collection work. Three subtasks of mechanized waste collection were identified, namely driving, bin collection, and egress and access of the vehicle. Spinal, shoulder, and upper limb kinematics along with surface electromyography from three muscles were collected during these tasks in a typical work shift. During driving and bin collection, participants adopted a head-extended, torso forward-flexed posture with frequent rotations of the head and neck. Egress and access of the vehicle produced substantially larger ranges of movement compared with driving and bin collection. The forward-flex, sitting posture can increase the risk of low back pain if there are undulations in the terrain and if this posture is adopted for prolonged periods. The frequent head and neck rotations can increase the incidence and severity of neck pain. Prolonged driving has been linked with an increased cardiometabolic risk and egress and access has increased risk of trips and falls from a height. Managers of waste collection workers should consider implementing interventions to reduce the exposure of this important workforce to the deleterious demands of their work.